Distance aware route algorithm for cloud computing based on CAN - HAN Zhi-jie1; HUANG Liu-sheng1; WANG Ru-chuan2; SUN Li-juan2; SHENG Ming1 (Tongxin xuebao)
Based on the traditional CRP mechanism,a new mechanism called M-CRP which is more adapt to the cloud computer mechanism was advanced.Based on traditional CAN,a new mechanism called M-CRP-CAN which make full use of M-CRP and make not only the CAN framework structure award of the physical location of nodes was advanced,but also the routing mechanism give more thought about the physical topology.The self-adaption can make the M-CRP-CAN has more ability to change according to the net status.In network simulation platform,the experimental results show that M-CRP’s performance is better than CRP in aspect of efficiency and precision.This M-CRP improves CRP from aspect of efficiency,precision and performance with multi-level mechanism,which make the node in cloud,has more perception to the underlying topology.In the meantime the M-CRP-CAN with M-CRP approach has realized localization download and greatly raised the data transfer rate,reduced the cross-traffic in backbone network and improve the network performance therefore enhance cloud computing system efficiency.